EVALUASI PEMBANGUNAN PERUMAHAN CITRALAND DENPASAR - Putera, I Gusti Agung Adnyana; Dewi, Anak Agung Diah Parami; Nugraha, Fransiskus Asisi Andi (JURNAL SPEKTRAN, 2020)
Population of Denpasar municipality has been significantly increasing for the last few years, with growth rate of 4.25% per year. This growth also increases the need of livable housing. Addressing this phenomenon, PT Citraland Development, Tbk., in collaboration with PT Karya Makmur, develop a residence area, named Citraland Denpasar. The development of residence area is a multi-stage prject until 2020. Hence, there is spared land for each house type to be built. Objective of this study is to maximize the sales profit of each type of house within limited remaining space. Furthermore, this study evaluates the financial aspect of the project by determining NPV, BCR, and IRR values. Evaluation of engineering aspect will also be covered, in term of Building Cost Ratio, Floor Area Ratio, Green Open Space, and foundation bearing capacity. Optimization analysis is done with linear program by WinQSB software. The result shows thar for the next project phase (2017-2020), maximum profit will be achieved by 30 units of Klenze type, 23 units of Jean type, 26 units of Danburite type, 30 units of Ives type, 26 units of Haydn type, 23 units of Franz type, 19 units of Beryl type, and 15 units of Amethyst type. The maximum profit estimation gained is Rp 278,107,835,566.00. Financial evaluation shows that NPV is Rp 417,393,944,138.00 (NPV > company NPV, which value is Rp 150 billion), BCR is 1.4999 (BCR > 1), and IRR is 24.51% (IRR > company IRR, which value is 10%). Thus, this project is financially profitable. Technically, Building Coverage Ratio value is 66.36% (BCR < 95%), Floor Area Ratio is 1.1456 (FAR < 3) and Green Open Space is 33.64% (GOS > 5%). This development project has complied statutory regulation. The foundation bearing capacity was measured to be 55.4 ton, while total load imparted to the foundation is 22.307 ton. Hence, the building meets safety requirement.